A tribute to Cicero Parker Meek. Issue 8 (December 2015) - Ottomann, C.; Hartmann, B.; Branski, L.; Krohn, C.
Highlights: Cicero Parker Meek was working as a general practitioner at the Aiken County Hospital in South Carolina, USA. He had a special interest in the treatment of burn patients. The Meek procedure for a device-based expansion of split-skin (micrografting) was invented before the mesh grafting. The technique first presented in 1958 by Meek is a milestone in the history of burn surgery. About the person of CP Meek, very little information has been found. Abstract: Cicero Parker Meek (1914–1979) was working as a general practitioner at the Aiken County Hospital in South Carolina, USA, and had a special interest in the treatment of burn patients. The procedure first presented in 1958 by Meek for a device-based expansion of split-skin (micrografting), which was invented before the mesh technique, is a milestone in the history of burns surgery. The method was forgotten until well into the 90s of the last century, and was only readopted and improved by no longer identifiable physicians at the Red Cross Hospital in Beverwijk. The Meek translation procedure was subsequently modified through the innovations of Kreis and Raff. With increased survival of massively burned patients, mesh grafting fell short of requirements. Mesh grafts of 1:9 expansion are difficult to handle and are vulnerable to dislodgement on the wound bed. Kreis and Raff showed in 1994 that 1:9 expanded mesh grafts did not achieve a true 1:9 expansion on the wound surface, in contrast to 1:9 expanded Meek grafts. Thus Meek grafts provided a highly effective autograft expansion in very large burns. Cicero Parker Meek was an exceptional person in the history of burn therapy.